Rwanda Economic Update, December 2018 : Schooling for Learning--Strengthening Resilience of Education in Rwanda - World Bank Group (World Bank, Kigali, 2018)
This is the 13th edition of the Rwanda Economic Update, a semiannual publication which reports on and synthesizes recent economic developments; considers them in a medium-term, regional, and global context; and analyzes how these developments and current policies may affect the outlook for the economy. This report attempts to make an analytical contribution to how Rwanda’s national development strategy is carried forward. Each edition also has a special feature spotlighting a particular topic. It is intended for a wide audience of policymakers, business leaders, other market participants, analysts engaged in Rwanda’s economy, and civil society.